Recognition of influenza A virus nucleoprotein by an H-2-restricted cytotoxic T-cell clone. - Townsend, A; Skehel, J; Taylor, P; Palese, P (1984)
Cytotoxic T-cell clones raised against X-31 (H3N2) influenza virus in C57BL/6 mice can be directed against an influenza A virus subtype specific determinant (1). A representative T-cell clone (A3.1) has been used in combination with a set of genetically typed recombinant viruses, to show that the A/PR/8/34 nucleoprotein can be responsible for cytotoxic T-lymphocyte recognition of infected target cells.